Registro do PEATE-FE com estímulo NB CE-chirp® LS utilizando o transdutor ósseo B-71 em crianças ouvintes e com perda auditiva condutiva - Freitas, Warlesson Gonçalves de (2018)
Introduction: In the last two decades researchers have concentrated on the construction of a new type of broadband stimulus and a narrowband version for the realization of the AEP-FS. Such studies are attempts to improve the amplitude as well as to reduce the time necessary to record the Potential Auditory Evoked test called chirp. Objective: To describe the latency, amplitude and minimum levels of response in the Bone-Conducted Brainstem Auditory Evoked Potentials recording, with the B-71 transducer in hearing children and with conductive hearing loss using the NB CE-Chirp® LS stimulus in the frequencies of 500 and 2000 Hz. Method: 14 children (22 ears) average age of 3.5 months were evaluated. The AEP-FS was recorded in the intensities of 10 to 50 dB nNA (maximum output of the equipment), always seeking the minimum level of each child response. The Radioear B-71 bone transducer was used with the manual method of fixation performed by a second experienced researcher. The latency averages in the two ears as well as the latency averages with the NB CE-Chirp® LS and Toneburst stimuli were compared by means of the Student t-test. Results: Bone conducted AEP-FS using the NB CE-Chirp® LS stimulus in the frequencies of 500 and 2000 Hz presented lower mean V-wave latencies and higher wavelength when compared to results obtained with the toneburst stimulus described in literature, mainly in the frequency of 500 Hz. No significant difference was observed in the latency and amplitude variables between the right and left ears. Conclusion: NB CE-Chirp® LS stimulation was promising in its use in the bone conducted AEP-FS. However, research with a larger number of subjects should be carried out in order to introduce normative values for its clinical usage